2011
DOI: 10.3390/md9071187
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activities of Sulfated Polysaccharides Isolated from Sphaerococcus coronopifolius (Rhodophytha, Gigartinales) and Boergeseniella thuyoides (Rhodophyta, Ceramiales)

Abstract: Water-soluble sulfated polysaccharides isolated from two red algae Sphaerococcus coronopifolius (Gigartinales, Sphaerococcaceae) and Boergeseniella thuyoides (Ceramiales, Rhodomelaceae) collected on the coast of Morocco inhibited in vitro replication of the Human Immunodeficiency Virus (HIV) at 12.5 μg/mL. In addition, polysaccharides were capable of inhibiting the in vitro replication of Herpes simplex virus type 1 (HSV-1) on Vero cells values of EC50 of 4.1 and 17.2 μg/mL, respectively. The adsorption step o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(93 citation statements)
references
References 69 publications
5
79
0
3
Order By: Relevance
“…Also these oligosaccharides have shown better diffusion ability in blood when fed in the experimental rats with oral heparin (Li et al, 2011). This study confirmed that oligosaccharide polymers such as dextrans possessing sulfate group might serve as natural alternatives in antiviral therapy leading to proper utilization of these inexpensive polysaccharides found abundantly in nature (Bouhlal et al, 2011). However, presence of other functional group other than sulfate might also have possibilities on the efficiency and antiviral properties of other types of polysaccharides.…”
Section: Modes Of Actionsupporting
confidence: 59%
See 3 more Smart Citations
“…Also these oligosaccharides have shown better diffusion ability in blood when fed in the experimental rats with oral heparin (Li et al, 2011). This study confirmed that oligosaccharide polymers such as dextrans possessing sulfate group might serve as natural alternatives in antiviral therapy leading to proper utilization of these inexpensive polysaccharides found abundantly in nature (Bouhlal et al, 2011). However, presence of other functional group other than sulfate might also have possibilities on the efficiency and antiviral properties of other types of polysaccharides.…”
Section: Modes Of Actionsupporting
confidence: 59%
“…This study revealed that protein bound polysaccharide may exert its partial antiviral mode of action against herpes simplex virus-2 virus via binding the glycoproteins of herpes simplex virus-2 virus to protein bound polysaccharide which may interfere at the initial state of virus replication or release of any virions. Similarly the sulfated polysaccharides dextran sulphate and heparin showed remarkable antiviral activity via their interaction with virus particle attachment to the host cell (Bouhlal et al, 2011). In addition, other sulfated polysaccharides including pentosan, polysulphate, sulphated cyclodextrins, xylofuranan sulphate, ribofuranan sulphate and mannan sulphate have also been found to exhibit inhibition of viral replication process for herpes simplex virus, human cytomegalo virus and human immunodeficiency virus (Bouhlal et al, 2011).…”
Section: Modes Of Actionmentioning
confidence: 97%
See 2 more Smart Citations
“…Among the marine organisms, the macroalgae (seaweeds) occupy an important place as a source of biomedical compounds [27]. Marine macroalgae are the most interesting algae group because of their broad spectrum of biological activities such as antimicrobial [9], anti-allergic [17], anticoagulant [4], cytotoxic [27], antiviral [3] and antioxidant activities [27]. As an aid to protect themselves against other organisms in their surrounding, macroalgae produce a wide variety of chemically active metabolites that have a broad range of biological activities.…”
Section: Introductionmentioning
confidence: 99%